The images of Oblivion (and Belatedness) from Nietzsche to Eco - Čale, Morana (Array, 2004)
The paper deals with the topic of oblivion as expounded by the literary works written over the last hundred-odd years which focus upon construing, explicitly or by synecdoche, a metaphorical imagery of Europeanness in its temporal dimension, thus elaborating in their own way the notions of narrativity and representation, authenticity and responsibility. Drawing on their modernist problematisation inaugurated by Nietzsche, the conceptual thinker Paul Ricoeur has recently discussed these issues within the framework of hermeneutics of human historical condition. I will argue that, in producing a particular narrative articulation grounded in the search for or the reconstruction of a lost personal identity, the narrative or dramatic enactment of the motif of amnesia forms a fictional strategy favoured by 20th century literature for the exploration of the particuliar predicament of modern Europeans, i.e. a state of mind determined by the past to such an extent that it can become all but unbearable. Significantly enough, the motif of the estranging disruption of individual memory, with its implied allegorical relation to a broader community history, emerges at various traumatic or crucial stages of Europe's historical trajectory. It is from the perspective of projected changes that the issue will be addressed.